Psychological Distress, Family Support and Employment Status in First-Year University Students in Spain - Arias-de la Torre, Jorge; Fernández-Villa, Tania; Molina, Antonio José; Amezcua-Prieto, Carmen; Mateos, Ramona; Cancela, José María; Delgado-Rodríguez, Miguel; Ortíz-Moncada, Rocío; Alguacil, Juan; Redondo, Susana; Gómez-Acebo, Inés; Morales-Suárez-Varela, María; et al. (International journal of environmental research and public health, 2019)
Mental disorders are consistently and closely related to psychological distress. At the start of the university period, the relationship between a student’s psychological distress, family support, and employment status is not well-known. The aims of this study were: To determine the prevalence of psychological distress in first-year university students and to analyze its relationship with family support and the student’s employment status. Data from 4166 first-year university students from nine universities across Spain were considered. The prevalence of psychological distress was obtained using the GHQ-12, a valid and reliable screening tool to detect poor mental health. To analyze the relationship between psychological distress, family support, and employment status, logistic regression models were fitted. Regarding the prevalence found, 46.9% of men and 54.2% of women had psychological distress. In both genders, psychological distress levels increased as family support decreased. Among women, psychological distress was associated with their employment status. The prevalence of psychological distress among first-year university students in Spain is high. In addition, family support, and employment status for women, could be factors to take into account when developing psychological distress prevention strategies at the beginning of the university period.